Rifampicin and isoniazid resistance not promote fluoroquinolone resistance in Mycobacterium smegmatis. - Qin Zhou; Na Pu; Ge Xu; Hangchi Liu; Xudong Jia; Xiaomin Wang; Peng Xu (PLoS ONE)
Background The emergence of drug-resistant Tuberculosis (TB) has made treatment challenging. Although fluoroquinolones (FQs) are used as key drugs in the treatment of multidrug-resistant tuberculosis (MDR-TB), the problem of FQs resistance is becoming increasingly serious. Rifampicin (RIF) resistance is considered a risk factor for FQs resistance. The objective of this study was to investigate the impact of RIF and isoniazid (INH) resistance on the FQs resistance in vitro experiment. Methods FQs resistant strains were selected in vitro from RIF and/or INH resistant Mycobacterium smegmatis (M.sm). The sequencing of the gyrA gene, and the minimum inhibitory concentration (MIC) of FQs (ciprofloxacin, levofloxacin, moxifloxacin and gatifloxacin) were performed for FQs-resistant strains. Results A total of 222 FQs-resistant M.sm strains were selected, all of which had the gyrA mutation. Seven gyrA mutations were detected, with mutations at loci 90 and 94 being the most common. There were no differences in FQs resistance developed from RIF and/or INH resistant M.sm. There was a significant difference in the MIC of the gyrA mutant types to FQs. The highest resistance to FQs was observed in the Gly88Cys mutant strains. M.sm with the identical gyrA mutation showed the highest resistance to ciprofloxacin and relatively low resistance to gatifloxacin and moxifloxacin. Conclusions In this study, we found no evidence that RIF and/or INH resistance directly affects FQs resistance in M.sm in vitro experiments. Resistance profiles of different gryA mutations to the four FQs drugs were also presented. These findings provide a more comprehensive understanding of FQs resistance.